Eruptive lentigines secondary to sunburn. - Milano, A. (European Journal of Pediatric Dermatology, 2018)
It is not easy to explain why the skin of the patient’s legs did not tan. It is easier to explain the appearance of eruptive lentigines. Meanwhile, in this case it seems important a genetic factor because the patient had very numerous lentigines on photoexposed areas. Furthermore, lentigines appeared after a sunburn; we known that the immune suppression can cause the appearance of lentigines and nevi (2). However, in this patient the lentigines appeared only on non-tanned skin. In the literature there are some cases of lentigines appearing on nevus depigmentosus (1) that have led some Authors to hypothesize a revertant mutation of genes responsible for melanocytic function. We also described a case of eruptive nevi on segmental vitiligo (2), but in that case the topical immune suppression linked to vitiligo therapy played a significant role.